Smart Data Recognition System For Seven Segment LED Display - Radzi, Syafeeza Ahmad; Hamid, Norihan Abdul; Wong, Yan Chiew; Ramli, Mimi Faisyalini; Noh, Zarina Mohd (International Journal of Human and Technology Interaction (IJHaTI), 2020)
The automatic data capturing system provides an alternative and effective way of data collection instead of manual data collection in the laboratory, especially for experiments that need to be carried out for a long period. It can solve common mistakes made by humans, like misreading or mistyping data. Thus, a new smart data recognition system for a seven-segment LED display is developed to sort the whole process of data collection to become more systematic and accurate. An image is captured and saved automatically in an image file, and then it is processed through MATLAB software to identify the digits displayed on the LED display. Once the image is preprocessed, analyzed, and recognized, the final output values obtained are transferred to an existing Excel file for a further process according to the user’s requirement. From the results obtained, it was proven that binary thresholding is the best preprocessing method, and the brightness of the image should be set to ‘0’ for better recognition output.